2011
DOI: 10.1097/bor.0b013e32834b5457
|View full text |Cite
|
Sign up to set email alerts
|

State of the art

Abstract: Understanding the causes of IIMs remains limited in part due to the rarity and heterogeneity of these disorders. Although no definitive studies have yet linked infectious agents with IIMs, additional evidence is accumulating and novel technologies may allow improved understanding of the roles of infections in IIMs and for possible future therapeutic and preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…In follow-up examinations, we found that myositis can persist for a long time, even when the patient responds well to steroid and immunosuppressive therapy. Because viral agents can cause idiopathic inflammatory myopathies, infection with the chikungunya virus might also trigger this type of condition in the long term (38) . Inflammatory involvement secondary to infection is a subject that has been discussed for some time, and the chikungunya virus has been associated with such involvement (34) .…”
Section: Discussionmentioning
confidence: 99%
“…In follow-up examinations, we found that myositis can persist for a long time, even when the patient responds well to steroid and immunosuppressive therapy. Because viral agents can cause idiopathic inflammatory myopathies, infection with the chikungunya virus might also trigger this type of condition in the long term (38) . Inflammatory involvement secondary to infection is a subject that has been discussed for some time, and the chikungunya virus has been associated with such involvement (34) .…”
Section: Discussionmentioning
confidence: 99%
“…This is a substantial limitation given that empirical approaches emphasize the importance of appropriate evidence being applicable to the specific patient or problem at hand (Gillam & Siriwardena, 2014). Nevertheless, failing to fully engage with clients who intend to use wearables as part of their treatment might lead to those clients seeking help elsewhere, or worse still, not at all (Coffey & Coffey, 2016). If nothing else, the use of wearables as an adjunct to therapy may potentially help through expectancy effects and increased engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Practice with calming technologies might therefore help to increase self-efficacy, reduce aversive interpretations of somatic arousal (Meuret, Wilhelm, & Roth, 2004), or even lead to lasting physiological changes (e.g., improved baroreflex function; Lehrer et al, 2003). Relaxation techniques already have an established place in the treatment of anxiety disorders (Manzoni, Pagnini, Castelnuovo, & Molinari, 2008), but given the rapid development and commercialization of wearables, little knowledge has been generated thus far about whether they could facilitate this approach to treatment (Coffey & Coffey, 2016). Nonetheless, despite the lack of existing evidence, numerous online reviews and opinion pieces offer enthusiastic endorsement for the use of these devices in improving well-being and addressing clinical disorders such as anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, arbovirus infections associated with skeletal muscle involvement and often subsequent neurological complications pose a particularly escalating threat in children (3235). Myositis disorders in humans are thought to be multifactorial diseases involving genetic factors and environmental triggers such as virus infections, yet these disorders remain poorly characterized with few treatment options available (8388). Thus, there is an urgent need to define better animal models to study virus-induced myositis.…”
Section: Discussionmentioning
confidence: 99%